Security analysis and portfolio management (PHI Learning Private Limited, 2020)
This well-organised, lucidly written text deals with the basic concepts of investment in securities such as bonds and stocks, and management of such assets. It not only discusses various aspects of portfolio management, ranging from analysis, selection, revision to evaluation of portfolio, but also elaborates on financial derivatives, securities market and risk evaluation that help in understanding the trading system better and making quality investment decisions. Besides explaining the theory of portfolio management that comprises fundamental and technical analyses, shares and bond valuation, efficient market theory and the capital asset pricing model, the book also provides a detailed analysis of the latest developments in securities trading